PERAN METODE DEBAT DALAM MENINGKATKAN KEMAMPUAN BAHASA INGGRIS SISWA KELAS VIII DI SMP ITech PASIM AR-RAYYAN - Sihabudin; Siti Qomariyah; Muhammad Helmi Alfian; Dwi Suryani Kurniawan; Siti Zainab (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the implementation of the English debate method in improving the English language skills of eighth-grade students at SMP ITech PASIM Ar-Rayyan. The debate method is one of the active learning methods that emphasizes speaking skills, expressing opinions, constructing arguments, and direct communication interaction using English. In English learning, this method is very important because students are not only required to understand the material theoretically, but also to actively, confidently, and communicatively use English in the learning process. This study employed a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The research subjects consisted of the principal and the English teacher at SMP ITech PASIM Ar-Rayyan. The results of the study indicate that the implementation of the English debate method was carried out through several stages, namely learning preparation, topic selection, group division, argument preparation, debate implementation, evaluation, and habituation of English use regularly. The implementation of the debate method was also supported by the English Day program held every Thursday and English khitobah activities after the Zuhur prayer. The implementation of the English debate method had a positive impact on students’ abilities, namely improving speaking confidence, speaking fluency, vocabulary mastery, active participation in learning, and self-confidence in using English. However, there were several obstacles in its implementation, such as differences in students’ English proficiency, the relatively longer time required, and the need for thorough preparation of learning materials before conducting the debate. Therefore, the implementation of the English debate method has proven to be effective and has a positive role in improving the English language skills of eighth-grade students at SMP ITech PASIM Ar-Rayyan.This study aims to determine the implementation of the English debate method in improving the English language skills of eighth-grade students at SMP ITech PASIM Ar-Rayyan. The debate method is one of the active learning methods that emphasizes speaking skills, expressing opinions, constructing arguments, and direct communication interaction using English. In English learning, this method is very important because students are not only required to understand the material theoretically, but also to actively, confidently, and communicatively use English in the learning process. This study employed a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The research subjects consisted of the principal and the English teacher at SMP ITech PASIM Ar-Rayyan. The results of the study indicate that the implementation of the English debate method was carried out through several stages, namely learning preparation, topic selection, group division, argument preparation, debate implementation, evaluation, and habituation of English use regularly. The implementation of the debate method was also supported by the English Day program held every Thursday and English khitobah activities after the Zuhur prayer. The implementation of the English debate method had a positive impact on students’ abilities, namely improving speaking confidence, speaking fluency, vocabulary mastery, active participation in learning, and self-confidence in using English. However, there were several obstacles in its implementation, such as differences in students’ English proficiency, the relatively longer time required, and the need for thorough preparation of learning materials before conducting the debate. Therefore, the implementation of the English debate method has proven to be effective and has a positive role in improving the English language skills of eighth-grade students at SMP ITech PASIM Ar-Rayyan.